Creating English Speaking Culture with EMI in English as Foreign Language (EFL) Classrooms - Indriani, Siane (Pusat Pelatihan, Riset, dan Pembelajaran Bahasa, 2025)
Due to the use of English worldwide as a lingua franca and to keep up with the global trend of teaching English as a Medium of Instructions (EMI), this has brought diverse responses and perspectives on how English should be perceived. For educational institutions, having English as a medium of instructions in the classes could be very challenging, moreover with the fact that English is not the native language of Indonesians. The language barrier for English learners might demotivate them to keep on learning and use English in daily interactions. Therefore, through qualitative research design the study aims to investigate and analyze how the use of EMI in classes brings transformations within and through them. Further, the study will also explore learners’ potentials through variety of strategies that will bring them to be reflective and responsive learners in facing any challenges, including language barriers in English learning process. Through class observations, questionnaires, and in-depth interviews, it was hoped that While EMI is often positioned as a strategy for global competitiveness, its success depends on how learners experience language use, identity affirmation, and emotional safety in the classroom. This study explores how EMI can be leveraged to foster a supportive English-speaking culture among preservice teachers in Indonesia. Drawing on qualitative data from classroom observations, questionnaires, and interviews, the research highlights the transformative potential of EMI when paired with culturally responsive and emotionally resonant pedagogies. Findings suggest that confidence-building strategies, translanguaging practices, and reflective tasks are keys to nurturing learner agency and sustained English use.